2017
DOI: 10.1016/j.jped.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Do infants with cow's milk protein allergy have inadequate levels of vitamin D?

Abstract: Lower vitamin D levels were found in infants with CMPA, especially those who were exclusively or predominantly breastfed, making these infants a possible risk group for vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Previous studies have indicated a heightened risk of low serum 25(OH)D in patients with CMPA that are breastfed and not on fortified hypoallergenic formulas [10,[34][35]. Surprisingly, in our study, partially breastfeeding children did not have significantly lower serum 25(OH)D levels than peers on hypoallergenic formulas.…”
Section: Breastfeeding Status and Vitamin D Supplementationcontrasting
confidence: 84%
See 2 more Smart Citations
“…Previous studies have indicated a heightened risk of low serum 25(OH)D in patients with CMPA that are breastfed and not on fortified hypoallergenic formulas [10,[34][35]. Surprisingly, in our study, partially breastfeeding children did not have significantly lower serum 25(OH)D levels than peers on hypoallergenic formulas.…”
Section: Breastfeeding Status and Vitamin D Supplementationcontrasting
confidence: 84%
“…The reported (80.8%) and actual (44.4%) rates of adherence to VDS among children with CMPA in Ireland fell within the range reported by previous studies [10,39,40] among children ≤ 24 months of age. National recommendations seem to play a limited role in encouraging VDS use.…”
Section: Vitamin D Supplementation Among Children With Cmpa In Irelandsupporting
confidence: 79%
See 1 more Smart Citation
“…The role of genetics in resistance vs. susceptibility to develop sesame allergies needs to be determined. Knowledge about what kind of environmental factors favor development of sesame allergy are largely unknown [97][98][99][100][101][102][103][104][105].…”
Section: How To Advance the Basic Preclinical And Clinical Researchmentioning
confidence: 99%
“…Several exposure conditions (e.g., environmental toxicants, triclosan, parabens, food preservatives, misuse of antibiotics, Vitamin D deficiency, sunlight exposure, dog ownership, excess use of antacids etc.,) that are currently being explored for other food allergies should provide the starting points of research [97][98][99][100][101][102][103][104][105].…”
Section: How To Advance the Basic Preclinical And Clinical Researchmentioning
confidence: 99%